High-bioactivity human-derived I-type collagen variant, composite material based on high-bioactivity human-derived I-type collagen variant and preparation method
By fusing the adhesion domain GPP into a collagen variant and combining it with PCL, a composite material of highly bioactive human type I collagen variant and PCL was prepared. This solved the problem of the imbalance between mechanical strength and physiological function of collagen-based materials in the prior art, achieving a balance between high mechanical strength and bioactivity, and expanding its application in tissue engineering and clinical practice.
Patent Information
- Application Number
- CN202511193132.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2025-11-28
AI Technical Summary
In existing collagen-based biomaterials, recombinant collagen fragments have weak self-assembly capabilities, and an excessively high PCL ratio can reduce the hydrophilicity and cell activity of composite materials, making it difficult to balance mechanical strength and physiological function.
A highly bioactive human type I collagen variant and PCL composite material was prepared by using a highly stable COL1 variant, fusing the adhesion domain GPP, and compounding it with PCL in a certain proportion, through expression and purification by Pichia pastoris.
It achieves high mechanical strength and bioactivity in composite materials of highly bioactive human type I collagen variants and PCL, promoting osteogenic differentiation and wound healing, and is suitable for tissue engineering scaffolds, wound dressings or bone repair materials.
Smart Images

Figure CN121021707A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials, and in particular to a highly bioactive human type I collagen variant, a composite material based thereon, and a method for its preparation. Background Technology
[0002] Collagen is an extracellular matrix protein found throughout the human body, possessing a variety of important biological functions. Type I collagen (COL1) is the most abundant type of collagen in the human body, primarily found in skin, bones, tendons, ligaments, and other connective tissues. It plays a crucial role in providing structural support and promoting the reconstruction of damaged tissues, making it a promising self-assembling biomaterial in tissue engineering. In recent years, collagen-based biomaterials have gained commercial acceptance and have been used to develop novel collagen-based materials for skin health, blood clotting, wound healing, and regenerative medicine applications. However, direct extraction of collagen from animal sources often results in impurities and potential immunogenicity, driving the demand for the production of human collagen using microbial systems (including bacteria and yeast). Furthermore, although microbial expression systems have been developed, full-length human COL1, as a functional viscoelastic biomolecule, is difficult to express, while short collagen fragments lack sufficient mechanical strength, limiting its clinical application. Therefore, it is necessary to identify novel COL1 fragments that can retain functional biological activity and are easily synthesized using microbial platforms, and to balance the biological activity and mechanical strength of biomaterials through the self-assembly of short collagen fragments and composite material methods, so as to provide a promising approach for the research and development and application of collagen-based biomaterials.
[0003] Polycaprolactone (PCL) is a synthetic, biodegradable linear aliphatic polyester. Among the various factors influencing collagen function, mechanical strength plays a crucial role in supporting its bioactivity and promoting cell adhesion. PCL has been widely used to enhance the strength of hybrid scaffolds due to its excellent mechanical properties. Compared to collagen, PCL exhibits significantly higher tensile strength and is biodegradable under physiological conditions. When integrated with bioactive materials such as collagen, PCL can provide structural support while preserving the physiological function of the composite material; however, the ratio of PCL to bioactive materials significantly affects the tissue structure of the composite. Therefore, it is essential to identify a ratio that balances mechanical strength and physiological function.
[0004] Existing collagen-based protein materials exhibit weak self-assembly capabilities of expressed recombinant collagen fragments, and excessively high PCL ratios reduce the hydrophilicity and cell viability of the composite materials. However, the inventors discovered during the development of collagen-based biomaterials that by screening for highly stable COL1 variants and fusing them with adhesion domains (GPPs) and optimizing the PCL ratio to create composite materials, these materials exhibit higher mechanical strength and bioactivity compared to standalone collagen variants. Therefore, it is necessary to propose a highly bioactive humanized collagen-PCL composite material and its preparation method to expand the applications of collagen-based biomaterials in tissue engineering and clinical settings. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to address the shortcomings of the prior art by providing a highly bioactive human type I collagen variant, a composite material based thereon, and a method for its preparation.
[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: In its first aspect, the present invention provides a highly bioactive human type I collagen variant, characterized in that its amino acid sequence includes a COL109 sequence and an adhesion domain fused to the COL109 sequence; said adhesion domain is a (GPP) composed of n repetitions of the amino acid sequence GPP. n Structural domain, where n is 5-20;
[0007] The COL109 sequence is: GAPGPSGARGERGFPGERGVQGPPGPAGPR (SEQ ID No. 9).
[0008] Preferably, n = 10.
[0009] Preferably, the adhesion domain is located at the N-terminus and / or C-terminus of COL109.
[0010] A second aspect of the invention provides a gene encoding the COL109 sequence in a highly bioactive human type I collagen variant as described above.
[0011] In a third aspect, the present invention provides a recombinant expression vector comprising the gene as described above, and a Pichia pastoris secretory expression element, such as the AOX1 promoter, α-MF signal peptide, etc.
[0012] A fourth aspect of the present invention provides a composite material based on a human type I collagen variant, characterized in that it comprises, as described above, a highly bioactive human type I collagen variant and polycaprolactone (PCL), wherein the mass ratio of the highly bioactive human type I collagen variant to PCL is (1:1) to (1:3).
[0013] Preferably, the mass ratio of highly bioactive human type I collagen variant to PCL is 1:1.
[0014] A fifth aspect of the present invention provides a method for preparing the composite material as described above, comprising the following steps:
[0015] S1, GPP n The domain is fused to the N-terminus and / or C-terminus of the COL109 sequence, and a His6 tag and a thrombin restriction site are fused to the N-terminus of the COL109 sequence to obtain the fusion sequence;
[0016] S2. By expressing the fusion sequence in Pichia pastoris, a collagen variant, namely a highly bioactive human type I collagen variant, is obtained through secretion.
[0017] S3, Collagen variant treatment: The secreted collagen variant was purified by affinity chromatography, and then the purification tag was removed by TEV protease digestion to obtain the purified collagen variant.
[0018] S4. The purified collagen variant is compounded with polycaprolactone at a mass ratio of (1:1) to (1:3) to prepare the composite material.
[0019] Preferably, the concentration of the highly bioactive human type I collagen variant in the composite material is maintained at a constant 5 g / L. When applying this composite material, it is dissolved in a solvent at a concentration of 5 g / L, and then introduced into a mold to prepare a gel forming the desired product shape. The solvent used can be hexafluoroisopropanol (HFIP), which is an ideal co-solvent for dissolving collagen and PCL. It can break the hydrogen bonds of proteins and the ester bonds of polymers, allowing the molecular chains of both to fully extend and mix, forming a homogeneous composite material.
[0020] A sixth aspect of the invention provides the use of the composite material described above in the preparation of tissue engineering scaffolds, wound dressings, or bone repair materials.
[0021] According to the above technical solution, the His6 tag is a commonly used biotechnological tool, typically used for protein purification and detection. This tag consists of six histidine residues (His) and is usually added to the N-terminus or C-terminus of the target protein in genetic engineering. The His6 tag can bind to nickel or cobalt ions, facilitating the purification of the target protein via affinity chromatography.
[0022] According to the above technical solution, the TEV enzyme (Tobacco Etch Virus protease) is an enzyme widely used in molecular biology and protein purification. It has specific cleavage sites and belongs to the serine protease family. The characteristic of TEV enzyme cleavage is that it recognizes and cleaves specific amino acid sequences, typically "ENLYFQ*G", where "*" indicates the cleavage site. In the expression and purification of recombinant proteins, the TEV cleavage site is often inserted between a tag (such as a His tag) and the target protein. The tag is then removed by cleavage with the TEV enzyme to obtain the purified target protein.
[0023] According to the above technical solution, by (GPP) n The resulting adhesion domains can enhance the formation of triple helices in fused collagen structural domains. (GPP) 10 They can be assembled into a triple helix, which has been confirmed by crystallography.
[0024] According to the above technical solution, polycaprolactone (PCL) is an important synthetic biodegradable polymer material. With its excellent flexibility, biocompatibility and relatively controllable slow degradation rate, it occupies a core position in the biomedical field (especially drug sustained release and tissue engineering scaffolds). Combining it with collagen variants can enhance its mechanical strength.
[0025] The beneficial effects of this invention are:
[0026] This invention provides a highly bioactive human type I collagen variant, a composite material based thereon, and a preparation method thereof. The COL109 / PCL composite material provided by this invention (i.e., a composite material based on a human type I collagen variant) exhibits higher mechanical strength compared to individual collagen variants, while maintaining high bioactivity, and can promote osteogenic differentiation and wound healing. This composite material has broad application prospects in the preparation of tissue engineering scaffolds, wound dressings, or bone repair materials. Attached Figure Description
[0027] Figure 1 The results of molecular weight analysis of ten variants from COL101 to COL110 by SDS-PAGE protein electrophoresis;
[0028] Figure 2 To analyze extracellularly expressed COL109(GPP) fused with the adhesion domain by SDS-PAGE protein electrophoresis. 10 The molecular weight test results of two collagen variants, C109(GPP)8;
[0029] Figure 3 For COL109(GPP) 10 COL109(GPP) 10The composite material PCL / COL109(GPP) prepared by mixing PCL and PCL at a 1:1 ratio 10 SEM image;
[0030] Figure 4 For different COL109(GPP) 10 Photographs of hydrogels formed from samples with different variants and PCL ratios;
[0031] Figure 5-7 For different COL109(GPP) 10 Rheological analysis results of samples with variants and PCL ratios. Figure 5 , 6 7. COL109 (GPP) 10 The ratios of PCL to PCL are 1:1, 1:2, and 1:3, respectively.
[0032] Figure 8 For different proportions of COL109 (GPP) 10 The water absorption capacity test results of PCL composite materials;
[0033] Figure 9 To use COL109 (GPP) in different proportions 10 A schematic diagram showing the proliferation rate of MC3T3-E1 cells cultured on a composite material prepared by PCL after 3 days of incubation.
[0034] Figure 10 To use COL109 (GPP) in different proportions 10 MC3T3-E1 cells were cultured on a composite material prepared by PCL, and the mRNA level of VCL, a marker associated with cell adhesion and cytoskeleton organization, was measured.
[0035] Figure 11 Using different proportions of COL109 (GPP) 10 MC3T3-E1 cells were cultured on a composite material prepared by PCL, and the mRNA levels of ACTN, a marker associated with cell adhesion and cytoskeleton organization, were measured.
[0036] Figure 12 To use COL109(GPP) at a ratio of 1:1 10 Healing ability test results of / PCL composite material. Detailed Implementation
[0037] The present invention will be further described in detail below with reference to embodiments, so that those skilled in the art can implement it based on the description.
[0038] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.
[0039] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials and reagents used in the following examples are commercially available. For examples where specific conditions are not specified, conventional conditions or conditions recommended by the manufacturer are followed. For reagents or instruments whose manufacturers are not specified, they are all commercially available products.
[0040] Example 1
[0041] The screening and expression of the recombinant collagen fragment COL109, and the verification of its self-assembly ability, included the following steps:
[0042] Step 1: A collagen fragment containing 30 amino acids was extracted from human COL1, and its Tm value was predicted using the deep learning model ColNet. Analysis showed no significant correlation between Tm value and net charge, hydrophobicity, or bioactivity. Therefore, Tm was used as a preliminary screening criterion to ensure the selected collagen fragments had self-assembly potential. After obtaining the prediction results, 100 fragments were selected as candidates based on their Tm values, from highest to lowest.
[0043] Step Two: Analysis revealed a strong Pearson correlation coefficient (PCC) of 0.93 between hydrophobicity and bioactivity, while no significant correlation was found between net charge and hydrophobicity. Based on this, a second round of screening used net charge values as the criterion to select the top 50 fragments with the highest net charge values.
[0044] Step 3: In the third round of screening, based on the predicted bioactivity, 10 candidate fragments were finally obtained.
[0045] Step 4: The 10 selected collagen fragments were named COL101 to COL110 and recombinantly expressed in Pichia pastoris by integration into the HIS4 locus. To enhance stability, each fragment was repeated 16 times. A His6 tag and a thrombin restriction site were fused to the N-terminus of the collagen domain for purification and subsequent tag removal.
[0046] Step 5: Using Pichia pastoris for expression, after 120 hours of fermentation, three variants, COL101, COL107, and COL109, were successfully secreted, and clear protein bands corresponding to their molecular weights were detected in the extracellular fraction. Figure 1 The expression levels ranged from 39 to 56 mg / L, with C109 showing the highest yield. The results indicate that the screened collagen fragments can be effectively expressed and secreted by Pichia pastoris.
[0047] Step Six: The three secreted collagen variants were purified using affinity chromatography, followed by TEV protease digestion to remove the purification tag. A hot-cold treatment was applied to remove unwanted proteins, and the sample was then filtered through a dialysis membrane.
[0048] Step 7: Verify self-assembly capability using CD spectroscopy. CD analysis at 4°C showed a positive peak at 220 nm and a negative peak at 195 nm for all three samples, indicating the formation of the characteristic triple helix structure of collagen samples, proving that all three variants have self-assembly capability.
[0049] Step 8: Thermal transition behavior was assessed by gradually increasing the temperature during CD measurements. The Tm values of the three variants ranged from 11.1 °C to 26.1 °C, with samples COL101 and COL109 maintaining their triple-helix conformation at temperatures above 15 °C. These results indicate that the recombinant collagen fragments are capable of self-assembly; therefore, two variants with relatively high Tm values were selected for further investigation.
[0050] Step Nine: The formation of triple-helix structures is crucial for achieving higher-order assembly. To evaluate this property, the self-assembly behavior of collagen variants was observed using TEM. Samples were prepared at a concentration of 1 g / L and incubated at 4°C for 3 days (using PBS buffer at pH 7.5 as the solvent). COL101 and COL109 formed nanofibers with widths of approximately 33 nm and 45 nm, respectively.
[0051] Step 10: To assess the potential of collagen variants to form hydrogels, samples were prepared at concentrations of 1 g / L and 5 g / L (using PBS buffer at pH 7.5 as the solvent and incubated at 4°C for 7 days). Both variants at a concentration of 5 g / L formed hydrogels within 24 hours, while all COL107 samples at a concentration of 1 g / L failed to form hydrogels.
[0052] Step 11: Rheological analysis of the hydrogels formed by the two collagen variants was conducted to assess their viscoelasticity. The storage modulus (G') values of both COL101 and COL109 exceeded their loss modulus (G”). The experiment revealed that the difference between G' and G” was greater for COL109, indicating that its gel network was stronger and possessed optimal self-assembly ability.
[0053] Table 1. Sequence and performance test results of 10 COL fragments selected from human COL1.
[0054]
[0055] Example 2: Adhesion domain fusion of collagen variants
[0056] This embodiment provides a method for constructing a collagen variant with enhanced mechanical strength, using (GPP) 10 The sequence was fused to the N-terminus and C-terminus of COL109 to construct COL109(GPP). 10 Its performance was verified by CD and rheology, including the following steps:
[0057] 1. Genetic modification of collagen variant COL109
[0058] The collagen variant COL109 was integrated into the HIS4 locus and recombinantly expressed in Pichia pastoris. To enhance stability, each fragment was repeated 16 times. Adhesion domains, including GPP repeated 8 and 10 times, were fused to the N-terminus and C-terminus of COL109, respectively, yielding two distinct constructs, including COL109(GPP). 10 And C109(GPP)8. Subsequently, a His6 tag and a thrombin cleavage site were fused to the N-terminus of the collagen domain to facilitate purification and subsequent tag removal.
[0059] 2. COL109(GPP) 10 Expression and purification
[0060] After fermentation with Pichia pastoris for 120 hours, including COL109(GPP) 10 Two variants, including C109(GPP)8, were successfully secreted, showing clear bands on SDS-PAGE consistent with the expected molecular weight. Figure 2 Two secreted collagen variants were purified using affinity chromatography, followed by TEV protease digestion to remove the purification tag. Undesirable proteins were removed by heat-cold treatment, and samples were then filtered using a dialysis membrane. All samples were prepared in water at a concentration of 0.1 mg / mL and preferentially incubated at 4°C prior to CD spectroscopy analysis.
[0061] 3. Fusion Adhesion Domain GPP 10 Performance validation of collagen variants
[0062] For performance verification, CD spectral analysis was performed using a Chirascan equipped with a Peltier temperature controller. TM The analysis was performed using a CD spectrometer (Applied Photophysics Ltd., Leatherhead, UK). Samples were loaded into quartz cuvettes (model 110-OS; optical path length 1 mm). CD spectra were collected in the wavelength range of 190 to 250 nm. The formation of the triple helix of the samples was verified by CD spectroscopy, demonstrating that the two samples could self-assemble.
[0063] To evaluate the ability of the collagen variant to form hydrogels, samples were prepared at a concentration of 5 g / L and incubated at 4°C for 7 days. The 5 g / L COL109 collagen variant pre-formed a hydrogel within 24 hours. The formed hydrogel was placed on a lower measuring plate. Ensuring good contact between the gel and the plate surface, without gaps or air bubbles, the upper plate was slowly lowered to the set gap (e.g., 0.5 mm). The strain range in which G' and G” remain substantially constant was identified by amplitude sweep (Strain / Amplitude Sweep). Safe strain values (γ_LVER) within this range were recorded for subsequent testing (e.g., 0.5%, 1%, 2%). Within the linear viscoelastic region (LVER) of the hydrogel, G' and G” were measured and analyzed by small amplitude oscillating shear (SAOS) testing.
[0064] Rheological analysis showed that, compared to 8 repetitions, 10 repetitions of the GPP contributed less to the higher storage modulus G'. Furthermore, the storage modulus G' was 2.2-2.3 times higher than the loss modulus G', exceeding that of the collagen domain alone. CD spectroscopy and rheological analysis indicated that fusing 10 repetitions of the adhesion domain GPP contributes to achieving higher mechanical strength.
[0065] Example 3: COL109 (GPP) 10 Preparation of PCL composite materials
[0066] COL109(GPP) 10 A porous scaffold is prepared by mixing PCL in a certain proportion and then freeze-drying, including the following steps:
[0067] Step 1: Expression of COL109(GPP) in Pichia pastoris 10 The collagen variant was purified by affinity chromatography, followed by TEV protease digestion to remove the purification tag. Unwanted proteins were removed by hot-cold treatment, and the sample was then filtered using a dialysis membrane.
[0068] Step 2: Replace the purified protein solution with lyophilization buffer (5mM sodium acetate, pH=5).
[0069] Step 3: Place the sample in an ultra-low temperature freezer at -80℃ for 8 hours to completely freeze it. Avoid freezing directly in the freeze dryer's cold trap (slow speed, large ice crystals).
[0070] Step 4: After pre-cooling the cold trap, start the freeze dryer and lower the cold trap temperature to -50°C. Quickly transfer the pre-frozen sample to the cold trap of the freeze dryer. Start the vacuum pump and reduce the chamber pressure to <0.1 mBar (100 mTorr). Maintain the cold trap temperature (-50°C) and the shelf temperature at -45°C for 36 hours.
[0071] Step 5: Perform secondary drying by slowly increasing the shelf temperature (2°C per hour) until it reaches 25°C, and maintain this temperature for 10 hours. This stage removes bound water. A good vacuum must be maintained.
[0072] Step Six: Determine the endpoint of the freeze-dried sample. The sample should be loose, porous, sponge-like or powdery, without any ice or wet areas. The freeze-drying curve should show that the product temperature is close to and remains stable near the shelf temperature. Then, break the vacuum and remove the sample by slowly filling the chamber with a dry, inert gas (such as nitrogen or argon), and then remove the freeze-dried protein powder sample.
[0073] Step 7: Prepare PCL stock solution in HFIP (hexafluoroisopropanol) (prepare an 8% w / v solution) to form a clear, viscous solution.
[0074] Step 8: Prepare COL109 (GPP) in HFIP. 10 Prepare the stock solution (3% w / v) by gently vortexing or briefly stirring (avoid vigorous stirring to prevent the introduction of air bubbles) until completely dissolved. Avoid prolonged high-speed stirring, which may cause molecular degradation or premature self-assembly.
[0075] Step Nine: Based on the target ratio (COL109(GPP)) 10 For PCL ratios of 1:1, 1:2, and 1:3 (w / w), slowly add COL109(GPP)10 stock solution to the PCL stock solution while gently stirring or vortexing.
[0076] Step 10: Carefully pour the well-mixed solution into the pre-cooled mold. Avoid introducing air bubbles; you can remove tiny air bubbles by gently tapping the edge of the mold or briefly centrifuging.
[0077] Step 11: Quickly immerse the mold containing the solution into liquid nitrogen (-196°C) and hold for several minutes until completely frozen. Then transfer it to a freeze dryer shelf for freeze-drying. Freeze for 60 hours to ensure the sample is completely dry (appearing as a loose, porous sponge with no wet areas).
[0078] Step 12: Completely immerse the lyophilized stent in the prepared EDC / NHS / MES crosslinking solution. Ensure the solution completely wets the interior of the stent. Incubate with gentle shaking at 4°C or room temperature for a specified time (12 hours).
[0079] Step 13: After the reaction is complete, remove the scaffold. Rinse with plenty of cold dH2O. Then soak and wash several times (1 hour each time) in 0.1M Na2HPO4 solution (or 0.1M Glycine solution). Rinse thoroughly with plenty of dH2O again. Finally, soak and wash with PBS to balance the pH and ionic strength, obtaining a porous scaffold.
[0080] Step Fourteen: Rheological analysis of the porous scaffold showed that increasing the proportion of PCL improved mechanical strength. At a 3:1 ratio, the composite exhibited the highest storage modulus (G'), exceeding the loss modulus (G”) by more than ten times. Even at a 1:1 ratio, the storage modulus was more than 8.7 times higher than the loss modulus, indicating the formation of a robust gel.
[0081] Reference Figure 3 This is COL109(GPP). 10 COL109(GPP) 10 The composite material PCL / COL109(GPP) prepared by mixing PCL and PCL at a 1:1 ratio 10 SEM image;
[0082] Reference Figure 4 For different COL109(GPP) 10 Photographs of hydrogels formed from samples of different variants and PCL ratios: Samples were prepared to 5 mg / mL and incubated at 4°C to form hydrogels, COL109(GPP). 10 The ratios of PCL to PCL are shown in the figure as 1:1, 1:2, and 1:3.
[0083] Reference Figure 5-7 For different COL109(GPP) 10 Rheological analysis results of samples with variants and PCL ratios: The samples were prepared to 5 mg / mL and incubated at 4 °C to form a hydrogel, and then rheological analysis was performed.
[0084] Step 15: Porosity analysis showed that as the PCL ratio increased, the water absorption rate decreased from 965% ± 33% to 473% ± 65%. Figure 8 This indicates that PCL is related to COL109(GPP). 10 The 1:1 ratio provides the best balance between mechanical strength and water absorption capacity.
[0085] Test Example 1 COL109(GPP) 10 Bioactivity testing of composite materials prepared with PCL
[0086] The bioactivity and differentiation-promoting ability of the composite materials with various ratios provided in Example 3 were verified through MC3T3-E1 cell experiments. The specific test methods are shown below:
[0087] First, mix the PCL stock solution with COL109 (GPP). 10 The stock solution (using hexafluoroisopropanol as the solvent) is prepared according to the target ratio (COL109(GPP)). 10Mixtures were prepared using PCL (1:1, 1:2, 1:3 w / w). Porous scaffolds were prepared according to the ratios, and after washing and pretreatment, they were ready for subsequent experiments. The cells required for the experiments were also prepared; MC3T3-E1 cells were cultured in Gibco minimum essential medium supplemented with 10% (v / v) fetal bovine serum and 1% (v / v) penicillin-streptomycin. TM The cells were cultured in Invitrogen (Shanghai, China). After completion, the cultured cells were incubated at 10... 4 Cells were seeded at high density into pre-prepared composite scaffolds and cultured (37°C, 5% CO2). After 4–6 hours, 500 μL of pre-warmed fresh complete culture medium was gently added, avoiding direct impact on the cells or scaffolds. Cells were washed with PBS after 3 days of incubation. Cell counts were performed using a CCK-8 assay kit. Relative Proliferation Rate (RPR) was calculated. Cell proliferation rates of different composite material formulations ranged from 334% to 353%, with a 1:1 ratio showing the best results (e.g., [missing information]). Figure 9 ).
[0088] To further evaluate the differentiation-promoting ability of the composite material, different proportions of the composite material COL109(GPP) were compared. 10 MC-3T3 cells (mouse embryonic osteoblasts, a type of pluripotent stem cell that can differentiate into various cell types such as osteoblasts, chondrocytes, and myocytes; under osteogenic differentiation conditions, MC3T3-E1 mouse embryonic osteoblasts can express osteoblast-specific genes and form calcified bone-like structures) were cultured on PCL (1:1, 1:2, 1:3) and collected by centrifugation. After obtaining the cells, total RNA was extracted using TRIzol reagent (Invitrogen Corporation, Carlsbad, CA, USA). Then, following the instructions of the One Step RT-qPCR kit (Sangon) and a QuantStudio 3 RT-qPCR instrument (Thermo Fisher, Shanghai, China), the RNA was reverse transcribed into cDNA. The DNA level was then quantitatively analyzed by RT-qPCR using a QuantStudio 3 RT-qPCR instrument (Thermo Fisher Scientific, Waltham, MA, USA), and the expression level was normalized relative to GAPDH expression.
[0089] Gene expression analysis showed that the mRNA levels of ACTN and VCL, markers associated with cell adhesion and cytoskeleton organization, peaked when a composite material of PCL and COL109(GPP)10 in a 1:1 ratio was used. Figure 10As the proportion of PCL increases, these levels decrease. Figure 11 These findings indicate that, despite exhibiting relatively low mechanical strength, the 1:1 composite material is most effective in promoting osteoblast differentiation. These results suggest that a 1:1 PCL / COL109(GPP) ratio is optimal. 10 The composite material can effectively promote cell proliferation and shows potential as a functional biomaterial for bone regeneration.
[0090] Test Example 2: PCL / COL109 (GPP) 10 Healing ability test of composite materials
[0091] The wound healing potential of the composite material provided in Example 3 was evaluated using cell migration experiments, and the specific test methods are as follows:
[0092] The ratio of PCL / COL109(GPP) is 1:1. 10 The composite material was applied to culture plates seeded with MC3T3-E1 cells. Wound gaps were created in the cell layer through mechanical scratching. After 24 hours of incubation, the gap closure rates of the composite material and the existing commercial COL1 reached 54% and 66%, respectively. Figure 12 By 36 hours, the closure rate of the composite group increased to 92%, and that of the commercial COL1 group increased to 85%. These results indicate that a 1:1 PCL / COL109 (GPP) ratio... 10 The composite material effectively promotes cell migration and wound healing, and its performance is comparable to that of commercial rat tail COL1.
[0093] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details.
Claims
1. A highly bioactive human type I collagen variant, characterized in that, Its amino acid sequence includes the COL109 sequence and an adhesion domain fused to the COL109 sequence; the adhesion domain is a (GPP) composed of n repetitions of the amino acid sequence GPP. n Structural domain, where n is 5-20; The COL109 sequence is: GAPGPSGARGERGFPGERGVQGPPGPAGPR (SEQ ID No. 9).
2. The highly bioactive human type I collagen variant according to claim 1, characterized in that, in, n=10。 3. The highly bioactive human type I collagen variant according to claim 1, characterized in that, in, The adhesion domain is located at the N-terminus and / or C-terminus of COL109.
4. A gene encoding the COL109 sequence in a highly bioactive human type I collagen variant as described in any one of claims 1-3.
5. A recombinant expression vector comprising the gene as described in claim 4, and a Pichia pastoris secretory expression element.
6. A composite material based on a human type I collagen variant, characterized in that, Includes the highly bioactive human type I collagen variant and polycaprolactone (PCL) as described in any one of claims 1-3, wherein the mass ratio of the highly bioactive human type I collagen variant to PCL is (1:1) to (1:3).
7. The composite material based on human type I collagen variant according to claim 6, characterized in that, The mass ratio of highly bioactive human type I collagen variant to PCL is 1:
1.
8. A method for preparing the composite material as described in claim 6 or 7, characterized in that, Includes the following steps: S1, GPP n The domain is fused to the N-terminus and / or C-terminus of the COL109 sequence, and a His6 tag and a thrombin restriction site are fused to the N-terminus of the COL109 sequence to obtain the fusion sequence; S2. By expressing the fusion sequence in Pichia pastoris, a collagen variant, namely a highly bioactive human type I collagen variant, is obtained through secretion. S3, Collagen variant treatment: The secreted collagen variant was purified by affinity chromatography, and then the purification tag was removed by TEV protease digestion to obtain the purified collagen variant. S4. The purified collagen variant is compounded with polycaprolactone at a mass ratio of (1:1) to (1:3) to prepare the composite material.
9. The preparation method according to claim 8, characterized in that, In the composite material, the concentration of highly bioactive human type I collagen variant is kept constant at 5 g / L.
10. The use of the composite material of claim 6 or 7 in the preparation of tissue engineering scaffolds, wound dressings or bone repair materials.